Legal Implications of Determining Red Zone Status on Land Ownership Rights - Sari, Novita; Tri Bawono, Bambang (Jurnal Konstatering, 2026)
This study aims to determine and analyze the legal implications of the determination of red zone status on land ownership rights in Tanah Laut Regency, to determine and analyze legal protection for land ownership rights owners. This study uses empirical legal research with a qualitative approach. Data were obtained through literature studies on laws and regulations and interviews with related parties, namely affected residents, BPBD TALA, PUPRP TALA and the Head of Kurau District. Based on the study, it can be concluded that the determination of the red zone does not eliminate land ownership rights, but limits these rights in accordance with the principle of social function as regulated in Article 6 of the UUPA. Legal protection for land rights owners, namely ownership rights are guaranteed by the UUPA, restrictions must be based on law, compensation rights, and recognition of ownership rights remain valid despite restrictions.